Electromagnetic Interference between Cranes and Broadcasting Antennas - V. Javor (International Journal of Antennas and Propagation)
An interesting phenomenon was noticed in some cases by workers operating with cranes in electromagnetic field of broadcasting antennas. They experienced electrical shock or burning pain at distances of kilometers away from powerful transmitters because cranes act as unintentional receiving antennas. The solution to this problem depends on dimensions and positioning of the crane structure, electromagnetic field strength at the site, frequency, and directional characteristic of the transmitting antenna. Electromagnetic interference between such structures is analyzed in this paper. Computational results for the induced currents and voltages in crane, treated as wire antenna problem, are determined using integrodifferential equations for the current along conductive structure, satisfying boundary condition for the electric field. Point matching method as the Method of Moments (MoM) is applied for solving these equations and polynomial approximation of the current is used. Results are presented for different crane structures and possible solutions to this problem are given.